Edukasi Trend Kejahatan Cyber Pada SMA Negeri 2 Baubau - Mashendra Mashendra; Safrin Salam; Amrun Kahar; Eko Satria; La Ode Muhammad Karim; Muhammad Sutri Mansyah; Abdul Rahim; Yayan Serah (Indonesian Journal Publisher, 2024)
In an increasingly digitally connected world, it is imperative to provide education on network and information technology crime trends. Where networks and information technology are an integral part of everyday life. Nevertheless, a small number of individuals are vulnerable to cybercrime, including data theft, phishing emails, and computer viruses, as a result of a lack of education and understanding of information technology trends. Therefore, it is imperative to have a comprehensive understanding of cybercrime threats, including phishing, scam/malware viruses, and Distributed Denial of Service (DDoS) attacks on a network. This will increase awareness and security in the use of information technology in the community, especially among students of SMA Negeri 2 Baubau, Southeast Sulawesi Province, Indonesia. The method used to implement abdimas for students of SMA Negeri 2 Baubau. This method consists of four stages: Laying the groundwork, planning, information gathering/analysis, and following up on findings The results of the students' CPD activities showed an increased awareness and understanding of cyber threats and how to protect themselves online. Indicators of success are changes in student behavior in safer internet use, such as changing passwords regularly and being more careful in sharing personal information online. It is hoped that this education on crime trends in the field of information technology and networking can be useful in developing self-awareness, self-protection, and mitigating the impact of cybercrime attacks in the digital realm.